Hepatitis B virus infection and the risk of cancer in the elderly US population. Issue 3 (28th November 2018) - Mahale, Parag; Engels, Eric A.; Koshiol, Jill
Abstract : Hepatitis B virus (HBV) infection causes hepatocellular carcinoma (HCC). Associations with other cancers are not established. We systematically assessed associations between HBV infection and cancers in the US elderly population. We conducted a case–control study using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare database in US adults aged ≥66 years. Cases ( N = 1, 825, 316) were people with first cancers diagnosed in SEER registries (1993–2013). Controls ( N = 200, 000) were randomly selected, cancer‐free individuals who were frequency‐matched to cases on age, sex, race and calendar year. Associations with HBV infection (ascertained by Medicare claims) were assessed by logistic regression. HBV prevalence was higher in cases than controls (0.6% vs . 0.5%). HBV was positively associated with cancers of the stomach (adjusted odds ratio [aOR] = 1.19; 95% confidence intervals [CI] = 1.03–1.37), anus (1.66; 1.17–2.33), liver (10.6; 9.66–11.6), intrahepatic bile ducts (1.67; 1.18–2.37), nasopharynx (2.08; 1.33–3.25), as well as myelodysplastic syndrome (1.26; 1.07–1.49) and diffuse large B‐cell lymphoma (DLBCL) (1.24; 1.06–1.46). Inverse associations were observed with female breast (aOR = 0.86; 95%CI = 0.76–0.98) and prostate (0.81; 0.73–0.91) cancers and chronic lymphocytic leukemia (0.77; 0.62–0.96). Associations were maintained in sensitivity analyses conducted in people without claims for cirrhosis or hepatitis C or human immunodeficiency virus infections. HBV infection is associated with increased risk of cancers other than HCC, such as bile duct cancers and DLBCL. The biological mechanisms by which HBV may lead to these cancers need to be explored. Abstract : What's new? Hepatitis B virus (HBV) infection is a known cause of hepatocellular carcinoma, but associations with other cancers remain unclear. The authors used the Surveillance, Epidemiology and End Results (SEER)‐linked Medicare database in the US to assess associations between HBV infection and cancers in the elderly. They found that HBV infection is also associated with other cancers, including of the biliary tract and diffuse large B cell lymphoma, findings that warrant further mechanistic studies.